Architectural heritage of the Amur Engineering Distance in the Khabarovsk Territory - Михаил Базилевич; Алина Иванова (Проект Байкал)
The article presents the intermediate results of the study conducted by the authors within the framework of grants from the Russian Science Foundation “Military Theme in the Architectural and Spatial Development of the Far East”. Brief historical information is provided on the structure and nature of the activities of the first construction organization in Khabarovsk Krai – the Amur Engineering Distance. Original projects and surviving buildings are considered. The authors highlight the significance of the architectural heritage sites of the Distance in the formation of the architectural landscape of the region.